PENGEMBANGAN MODUL PEMBELAJARAN SAINS BERBASIS KEARIFAN LOKAL DAERAH NGAWI PADA TAMAN KANAK-KANAK - Susdarwati Susdarwati; Degi Arlinda Agustina (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This research is based on the facts in the field that kindergarten teachers do not have teaching materials about the Science learning module based on local wisdom so that the cognitive abilities of children in the field of scientific ability and knowledge of local wisdom is still low. The purpose of this research are: 1) to produce product of the Science learning module based on local wisdom of Ngawi area and 2) to analyze the feasibility of the Science learning module based on local wisdom of Ngawi area. This research is Research and Development (R & D) by using 4-D model covering define stage, design, develop, and disseminate proposed by Thiagarajan. Data collection using questionnaire. The result of the research shows that: 1) The Science learning module based on local wisdom developed with the characteristic of curriculum 2013 is based on the scientific approach component with local wisdom of Ngawi area with the experimental method 2) The feasibility of the Science learning module based on local wisdom is feasible to be used based on the assessment by the expert lecturer 51.75 with category is very good. The result of the assessment of 9 kindergarten teachers of the module on the limited trial was 52.78 with very good category. The result of the assessment of 21 kindergarten teachers on the module on field trial was 57.05 with very good category of maximum score 60.